(untitled) (Bangladesh Journal of Botany, 2008)
Morphology and anatomy of Crocus speciosus Bieb. subsp. speciosus, C. speciosus Bieb. subsp. ilgazensis, C. speciosus subsp. xantholaimos were done. Two of them (subsp. ilgazensis and xantholaimos) are endemic to small areas of Turkey. The subsp. xantholaimos has flowers with tube stained yellow. The subsp. ilgazensis has a corm splitting into vertical fibres. These properties are characteristic for the two subspecies investigated. Cross-sections of root and aerial stem of three subspecies were examined and characterized. A key to the identification of the three taxa, based solely on anatomical features is provided here.